2017
DOI: 10.1016/j.jct.2017.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and evaluation of thermodynamic data for mirabilite-thenardite equilibria at 0.1 MPa

Abstract: Mirabilite and thenardite are common minerals found in marine evaporite deposits and also in saline lakes as precipitates. In this study, mirabilite-thenardite equilibria were determined along four humidity-buffer curves at 0.1 MPa and between 285.15 K and 305.15 K. Results for the reaction Na 2 SO 4 •10H 2 O (s) = Na 2 SO 4(s) +10 H 2 O (g) , based on tight reversals along each humidity buffer, can be represented by ln K = 174.032-62815.11/T, where s is solid, g is gas, K is the equilibrium constant and T is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Effect of temperature on solubility and the saturated solid-phase form of Na 2 SO 4 at 101.325 kPa. ▲, solubility data reported in the literature; ●, solubility determined in this work. Mir for mirabilite, Na 2 SO 4 ·10H 2 O; Th for thenardite, Na 2 SO 4 .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of temperature on solubility and the saturated solid-phase form of Na 2 SO 4 at 101.325 kPa. ▲, solubility data reported in the literature; ●, solubility determined in this work. Mir for mirabilite, Na 2 SO 4 ·10H 2 O; Th for thenardite, Na 2 SO 4 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…When the temperature is higher than 305.53 K, the mass fraction of Na 2 SO 4 almost reaches a plateau, and the equilibrium solid phase transfers into thenardite. 21 In other words, the mineral mirabilite becomes anhydrous to form thenardite when temperature exceeds 305.53 K.…”
Section: Resultsmentioning
confidence: 99%
“…Despite many studies on the crystallization of sodium sulfate over the last 150 years, the reason why it generates damage remains controversial. Sodium sulfate has two stable phases at room temperature, thenardite (an anhydride) and mirabilite (a decahydrate), as well as a metastable phase [35][36][37]. At low temperature, the solubility of sodium sulfate largely decreases so that the pore liquid in the stabilized soil reaches supersaturation, which is a necessary condition for the occurrence of crystallization pressure [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Flatt [19] and Wang et al [20] concluded that sodium sulfate crystals, sodium decahydrate crystals, and sodium sulfate solution coexist at 32.4°C and RH of 82.5%, as shown in Figure 1 [19,21]. When the temperature is greater than 32.4°C and the RH is less than the critical one, sodium sulfate decahydrate crystals lose water and become sodium sulfate crystals; vice versa, it absorbs water and becomes sodium sulfate solution.…”
Section: Introductionmentioning
confidence: 96%